Juridical Analysis of the Legal Protection of Workers / Laborers Against Termination of Employment That Is Not in Accordance with Law Number 6 of 2023 concerning Job Creation - Mathesta, Robbin; Wijayati, Ani; Saragi, Paltiada (Jurnal Indonesia Sosial Sains, 2024)
Law No. 6 of 2023 on Job Creation aims to encourage economic growth in Indonesia, but it also brings significant changes to labor regulations, including the expansion of the reasons for Termination of Employment. This research aims to analyze legal protection for workers who are laid off not in accordance with the provisions of the law. In addition, this study seeks to understand the challenges of protecting workers' rights in the midst of increasingly complex labor dynamics. The approach used is a normative approach, analyzing various related regulations, especially the Job Creation Law and the Employment Law. This study also examines the theory of legal certainty, justice, and legal protection as an analytical framework. Using a case study approach, this study analyzes the case of unilateral termination of employment at PT BFI Finance as a concrete example to assess the application of legal provisions in practice. The research method used is normative legal research with secondary data, including primary, secondary, and tertiary legal materials. The results of the study show that the Job Creation Law provides a clearer legal framework regarding the layoff procedure and legitimate reasons. However, there are challenges in the implementation and enforcement of the law that need to be overcome, considering that there is still a gap between legal provisions and practices in the field that can be detrimental to workers' rights. The research recommendations include the need for more intensive socialization to workers and employers about the new provisions, as well as consistent law enforcement to protect workers' rights.